2014
DOI: 10.1155/2014/213570
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis of Ovarian Granulosa Cell Transcriptome

Abstract: The quality of follicular oocytes depends on interactions with surrounding granulosa cells. Development of molecular techniques and methods enables better understanding of processes underlying mammalian reproduction on cellular level. The success in reproductive biology and medicine in different species depends on reliable assessment of oocyte and embryo viability which presently mainly bases on embryo morphology. Although successful pregnancies have been achieved using this approach, its precision still shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Endocannabinoids also target the peroxisome proliferator-activated receptors (PPARs) [ 33 ]; in particular, through the activation of PPARα or PPARγ [ 34 ], AEA and 2-AG can modulate lipid and glucose metabolism. This aspect is crucial in cumulus cells, since one of their key functions in the follicle environment is to sustain the metabolic needs of the oocytes, which are not independent [ 35 , 36 , 37 ]. Granulosa and cumulus cells have a role in follicular lipid metabolism regulation, by oxidizing lipids and storing them in lipid droplets [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endocannabinoids also target the peroxisome proliferator-activated receptors (PPARs) [ 33 ]; in particular, through the activation of PPARα or PPARγ [ 34 ], AEA and 2-AG can modulate lipid and glucose metabolism. This aspect is crucial in cumulus cells, since one of their key functions in the follicle environment is to sustain the metabolic needs of the oocytes, which are not independent [ 35 , 36 , 37 ]. Granulosa and cumulus cells have a role in follicular lipid metabolism regulation, by oxidizing lipids and storing them in lipid droplets [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the intimate connection between GCs and oocyte, it is clear that modifications in somatic components transcriptomes affect the oocyte functions and vice versa. The main approaches employed to study GCs transcriptome have been represented by microarray analysis and next-generation RNA sequencing [7]. These two approaches allow to study simultaneously thousands of transcripts and evidence the role of specific genes in normal and pathological oocyte development.…”
Section: Granulosa Cells Transcriptome Analysismentioning
confidence: 99%
“…Cumulus cells, which are layers of specialized granulosa cells encircling oocytes, are thought to be closely related to the growth and meiotic maturation of oocytes, not only through supplying nutrients or signaling molecules to oocytes via gap junctions [ 1 , 2 ] but also via the protection of oocytes from adverse environments or factors [ 3 ]. Notably, increasing evidence has demonstrated that apoptosis in cumulus cells plays a mediating role in impairing oocyte developmental potential [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%